Episiotomy repair in continuous versus interrupted suturing technique in primiparous women: A Randomized clinical trial - Marziyeh Loripoor; Pouran Allahbakhshi Nasab; Marziyeh Najar (Mashhad University of Medical Sciences, 2021)
Introduction: Episiotomy is associated with some complications such as pain, infection and discomfort of perineal sutures for mothers. This study was performed with aim to compare the complications of episiotomy repair in continuous versus interrupted suturing technique in primiparous women Methods: This single blind randomized clinical trial study was performed in 2017-2018 on 140 primiparous women referred for vaginal delivery in Niknfas maternity hospital in Rafsanjan city. The subjects were randomly divided into two groups (n=70 in each group). Repair of episiotomy was done in one group with interrupted and in another group with continuous suturing technique. The tools were demographic and midwifery characteristics form, visual analog scale and surgical site infection. Pain severity score, analgesia use, wound infection and discomfort stitches were assessed 2 hours, 3-5 days, 2 and 6 weeks after delivery. Data were analyzed using SPSS software (version 22) and Chi-square, Independent-t and Mann-Whitney tests. P<0.05 was considered statistically significant. Results: The pain severity score and discomfort stitches was lower in continuous group than interrupted group (p<0.05). Use of analgesia at these times was not significantly different between the two groups (p>0.05). Wound infection in 3-5 days and 2 weeks after delivery was lower in continuous group (p<0.05). Also, the repair time, number of threads and lidocaine used ampoules were less in the continuous method (p <0.05). Conclusion: Pain intensity, discomfort stitches and episiotomy infection were less in continuous method compared to interrupted repair; it seems cost-effective due to less use of threads and analgesia.